A Comparative Analysis of TPACK Mastery Among Novice, Intermediate, and Senior Physical Education Teachers - Iyan Nurdiyan Haris; Ernawati Ernawati; Tri Maniarta Sari; Rosti Rosti; Syarif Hidayat Nasir; Aqzhariady Khartha (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study investigates variations in Technological Pedagogical Content Knowledge (TPACK) mastery among novice (0–5 years), intermediate (5–10 years), and senior (>10 years) physical education teachers in Kolaka Regency, Indonesia, while exploring contextual factors that influence its implementation. Employing a sequential explanatory mixed-methods design, the research integrates quantitative survey data from 80 teachers with qualitative findings from classroom observations and semi-structured interviews. Quantitative analysis revealed significant differences in TPACK proficiency, with intermediate teachers achieving the highest mean score (M = 4.2), attributed to their optimal balance of pedagogical experience and adaptability to technological innovation. Qualitative data illuminated systemic challenges, including limited infrastructure and institutional support, particularly in rural areas. Teachers responded with adaptive strategies such as peer-based collaboration, frugal use of mobile technologies, and contextualized integration of cultural elements into digital instruction. These strategies formed a locally grounded “TPACK ecosystem,” driven by grassroots innovation rather than top-down mandates. The study highlights how teaching experience, socio-cultural context, and institutional constraints intersect to shape TPACK development. Findings emphasize the importance of differentiated professional development tailored to career stages, as well as the need for policy frameworks that formalize and support informal teacher networks. This research offers practical recommendations for enhancing technology integration in physical education, particularly in resource-constrained settings.